Math Problem Statement

MP2 (1).pdf

97.45 KB

can you answer this from top to bottom with complete solutions

Solution

Let’s address each question from the document systematically:


1. Proof by Mathematical Induction for P(n)P(n):

a. What is the statement P(1)P(1)?

P(1):12=1(1+1)(2(1)+1)6P(1): 1^2 = \frac{1(1+1)(2(1)+1)}{6}

b. Show that P(1)P(1) is true.

  • Left-hand side: 12=11^2 = 1
  • Right-hand side: 1(1+1)(2(1)+1)6=1(2)(3)6=1\frac{1(1+1)(2(1)+1)}{6} = \frac{1(2)(3)}{6} = 1
  • Since LHS=RHSLHS = RHS, P(1)P(1) is true.

c. What is the inductive hypothesis?

Assume P(k)P(k) is true: 12+22++k2=k(k+1)(2k+1)61^2 + 2^2 + \dots + k^2 = \frac{k(k+1)(2k+1)}{6}

d. What do you need to prove in the inductive step?

Prove P(k+1)P(k+1): 12+22++k2+(k+1)2=(k+1)((k+1)+1)(2(k+1)+1)61^2 + 2^2 + \dots + k^2 + (k+1)^2 = \frac{(k+1)((k+1)+1)(2(k+1)+1)}{6}

e. Complete the inductive step:

  1. Start from the hypothesis: 12+22++k2=k(k+1)(2k+1)61^2 + 2^2 + \dots + k^2 = \frac{k(k+1)(2k+1)}{6}
  2. Add (k+1)2(k+1)^2 to both sides: 12+22++k2+(k+1)2=k(k+1)(2k+1)6+(k+1)21^2 + 2^2 + \dots + k^2 + (k+1)^2 = \frac{k(k+1)(2k+1)}{6} + (k+1)^2
  3. Simplify the RHS: =k(k+1)(2k+1)+6(k+1)26= \frac{k(k+1)(2k+1) + 6(k+1)^2}{6} =(k+1)[k(2k+1)+6(k+1)]6= \frac{(k+1)\big[k(2k+1) + 6(k+1)\big]}{6} =(k+1)[2k2+k+6k+6]6= \frac{(k+1)\big[2k^2 + k + 6k + 6\big]}{6} =(k+1)[2k2+7k+6]6= \frac{(k+1)\big[2k^2 + 7k + 6\big]}{6} =(k+1)(k+2)(2k+3)6= \frac{(k+1)(k+2)(2k+3)}{6}
  4. This matches the formula for P(k+1)P(k+1).

Thus, by induction, P(n)P(n) is true for all n1n \geq 1.


2. Prove the Sum Formula:

Prove: 12+23++n(n+1)=n(n+1)(n+2)31 \cdot 2 + 2 \cdot 3 + \dots + n(n+1) = \frac{n(n+1)(n+2)}{3}

Proof by Induction:

  • Base case (n=1n = 1): 12=1(1+1)(1+2)3=1233=21 \cdot 2 = \frac{1(1+1)(1+2)}{3} = \frac{1 \cdot 2 \cdot 3}{3} = 2 LHS=RHSLHS = RHS, so true for n=1n = 1.

  • Inductive Hypothesis: Assume true for n=kn = k: 12+23++k(k+1)=k(k+1)(k+2)31 \cdot 2 + 2 \cdot 3 + \dots + k(k+1) = \frac{k(k+1)(k+2)}{3}

  • Inductive Step (n=k+1n = k+1): Add (k+1)(k+2)(k+1)(k+2) to both sides: 12+23++k(k+1)+(k+1)(k+2)=k(k+1)(k+2)3+(k+1)(k+2)1 \cdot 2 + 2 \cdot 3 + \dots + k(k+1) + (k+1)(k+2) = \frac{k(k+1)(k+2)}{3} + (k+1)(k+2) Factor (k+1)(k+2)(k+1)(k+2) on the RHS: [ = (k+1)(k+2)\big[\frac{k}{3} + 1\big] = (k+1)(k+2)\big[\frac{k+3}{3}\big] ] =(k+1)(k+2)(k+3)3= \frac{(k+1)(k+2)(k+3)}{3} This matches the formula for P(k+1)P(k+1).

By induction, the formula is true for all n1n \geq 1.


3. Evaluate f(n)f(n) for Recursively Defined Functions:

a. f(n+1)=f(n)+2,f(0)=1f(n+1) = f(n) + 2, f(0) = 1:

f(1)=1+2=3,f(2)=3+2=5,f(3)=5+2=7,f(4)=7+2=9f(1) = 1 + 2 = 3, f(2) = 3 + 2 = 5, f(3) = 5 + 2 = 7, f(4) = 7 + 2 = 9

b. f(n+1)=3f(n),f(0)=1f(n+1) = 3f(n), f(0) = 1:

f(1)=31=3,f(2)=33=9,f(3)=39=27,f(4)=327=81f(1) = 3 \cdot 1 = 3, f(2) = 3 \cdot 3 = 9, f(3) = 3 \cdot 9 = 27, f(4) = 3 \cdot 27 = 81

c. f(n+1)=2f(n),f(0)=1f(n+1) = 2f(n), f(0) = 1:

f(1)=21=2,f(2)=22=4,f(3)=24=8,f(4)=28=16f(1) = 2 \cdot 1 = 2, f(2) = 2 \cdot 2 = 4, f(3) = 2 \cdot 4 = 8, f(4) = 2 \cdot 8 = 16


4. Recursive Definitions:

a. an=6na_n = 6n:

a1=6,a2=12,a3=18,an+1=an+6a_1 = 6, a_2 = 12, a_3 = 18, a_{n+1} = a_n + 6

b. an=10na_n = 10n:

a1=10,a2=20,a3=30,an+1=an+10a_1 = 10, a_2 = 20, a_3 = 30, a_{n+1} = a_n + 10

c. an=2n+1a_n = 2n + 1:

a1=3,a2=5,a3=7,an+1=an+2a_1 = 3, a_2 = 5, a_3 = 7, a_{n+1} = a_n + 2


5. List Ordered Pairs for Matrices:

a.

Matrix:

1 & 0 & 1 \\ 0 & 1 & 0 \\ 1 & 0 & 1 \end{bmatrix}$$ Ordered pairs: $$(1, 1), (1, 3), (2, 2), (3, 1), (3, 3)$$ #### b. Matrix: $$\begin{bmatrix} 0 & 1 & 0 \\ 0 & 1 & 0 \\ 0 & 1 & 0 \end{bmatrix}$$ Ordered pairs: $$(1, 2), (2, 2), (3, 2)$$ #### c. Matrix: $$\begin{bmatrix} 1 & 1 & 1 \\ 1 & 0 & 1 \\ 1 & 1 & 1 \end{bmatrix}$$ Ordered pairs: $$(1, 1), (1, 2), (1, 3), (2, 1), (2, 3), (3, 1), (3, 2), (3, 3)$$ --- If you'd like a continuation with the remaining questions or additional clarifications, feel free to

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Mathematical Induction
Summation Formulas
Recursive Functions
Matrix Relations
Equivalence Relations
Poset Theory

Formulas

Sum of squares: 1^2 + 2^2 + ... + n^2 = n(n+1)(2n+1)/6
Summation of n(n+1): 1*2 + 2*3 + ... + n(n+1) = n(n+1)(n+2)/3

Theorems

Principle of Mathematical Induction
Properties of Equivalence Relations
Partial Order Set (Poset) Theory

Suitable Grade Level

Undergraduate level, Computer Science or Mathematics students